Influência da infecção pelo HIV e do uso da terapia antirretroviral nas concentrações de selênio, selenometionina e proteção antioxidante - Watanabe, Lígia Moriguchi [UNESP] (2015)
The antioxidant components deficiencies may hasten the progression of HIV disease increasing the oxidative stress, which has been associated with both use of antiretroviral therapy (ART) and HIV infection. Selenium has an important role in HIV infection mainly due to its involvement in oxidative stress regulation. Its beneficial effects are dependent on their chemical form and concentration, highlighting the importance of selenium speciation. The present study aimed to evaluate whether HIV infection and ART time of use are associated with increased oxidative damage, low concentrations of selenium and its metabolites, and reduced antioxidant protection of glutathione and glutathione peroxidase. This is a cross-sectional study consisted of 120 individuals that were classified as: Control Group (GC), HIV negatives, n=40; Group 1 (G1), HIV positives under ART for more than 5 years, n=40; and Group 2 (G2), HIV positives under ART for less than 5 years, n=40. Plasma selenium, erythrocyte selenium and selemethionine were evaluated. The antioxidant parameters were glutathione concentration and glutathione peroxidase activity. Oxidative stress was measured by malondialdehyde. In addition, we evaluated the dietary intake and anthropometry. The current analysis indicated that the subjects in this study had adequate selenium ingestion and the absence of plasma selenium deficiency was associated with the use of ART. We observed that HIV infection and use of ART influence oxidative stress, which in turn promotes an increase of the expression of antioxidant defenses, measured by glutathione and glutathione peroxidase. About selenomethionine, it is possible that its concentration increase is related to the chemical form of the ingested selenium and that the use of ART contributes to its decrease. However, further studies are necessary to understand the influence of ...